The political thought of Elizabeth Cady Stanton : women's rights and the American political traditions - Davis, Sue, 1948- (New York University Press, 2008)
"2009 Choice Outstanding Academic Title. Elizabeth Cady Stanton (1815-1902) was not only one of the most important leaders of the nineteenth century women's rights movement but was also the movement's principal philosopher. Her ideas both drew from and challenged the conventions that so severely constrained women's choices and excluded them from public life. In The Political Thought of Elizabeth Cady Stanton, Sue Davis argues that Cady Stanton's work reflects the rich tapestry of American political culture in the second half of the nineteenth century"--Provided by publisher